Psychotropic medication use trends in a large pediatric and young adult solid organ transplant population. (20th February 2019) - Samsel, Chase; Tapsak, Sara; Thomson, Katharine; McKenna, Kristine; McGregor, Kerry; Forbes, Peter; Ibeziako, Patricia
Abstract: Introduction: This study describes psychotropic medication use in a pediatric and young adult solid organ transplant population. Methods: We conducted a retrospective review of the lifetime incidence of psychotropic medication use and associated characteristics in patients seen over a 6‐year period at a large pediatric transplant center utilizing univariate and multivariate statistical analyses. Results: The lifetime incidence of psychotropic medication use was 36.5% in 393 patients. Transplant psychiatry provided psychopharmacological consultation to 21.9% of patients. Controlling for age and sex, there were significant associations between psychotropic use and thoracic organ disease (heart/lung) (AOR = 2.14; 95% CI: 1.2‐3.8; P  = 0.01), White race ( P  = 0.0002), histories of depressive/mood disorders (AOR = 3.68; 95% CI: 1.8‐7.7; P  = 0.0005), attention/learning disorders (AOR = 3.30; 95% CI: 1.6‐6.9; P  = 0.001), acute and post‐traumatic stress disorders (AOR = 10.54; 95% CI: 2.6‐42.8; P  = 0.001), and experiencing bullying (AOR = 2.16; 95% CI: 1.03‐4.55; P  = 0.04). In unadjusted tests, significant associations were found between lifetime psychotropic usage and patient anxiety history (OR = 2.26; 95% CI: 1.5‐3.5; P  = 0.0002), end‐of‐life disease progression (OR = 3.04; 95% CI: 1.7‐5.4; P  = 0.0002), family psychiatric history (OR = 2.17; 95% CI: 1.4‐3.4; P  = 0.0007), and adherence concerns (OR = 2.67; 95% CI: 1.7‐4.1; P  < 0.0001). Discussion: The lifetime incidence of psychotropic medication use among pediatric and young adult transplant patients is substantial. Patients with thoracic organ disease, end‐of‐life illness, individual/family psychiatric histories, trauma, and bullying histories have particularly high rates. Integrating child psychiatry as part of pediatric transplant teams should be an important consideration for the care of these patients.